(untitled) (Bulletin KNOB, 2001)
As an itinerant draughtsman, fortifications engineer, painter, and rhetorician, Hans Vredeman de Vries has never fit smoothly into 19th and 20th century historical narratives that insist upon the idea of ‘national schools’. The separation contemporary historians have often unwittingly placed between Vredeman’s work as a graphic designer and as an architect seems inconsistent with the reality of the sixteenth century, and is often predicated upon stylistic and periodic designations defined by the Italian Renaissance. This essay’s survey of historiography on Vredeman reveals a picture where 19th and 20th century authors are often at odds with writers from the 16th, 17th and 18th centuries, who appear less apt to draw sharp distinctions between Vredeman’s role as an architectural designer and artist. As pattern books, Vredeman’s series’ were by nature subject to widely varying uses and receptions, more so even than other types of prints bound to historical or propagandistic narratives. The market for and reception of Vredeman’s architectural books and print series during the sixteenth, seventeenth and eighteenth centuries is also characterized by exceptional diversity in terms of distribution and classification. During Vredeman’s stays in Antwerp between 1561-1570 and 1575-1586 demand for the new specialty of architectural prints appears to have remained relatively stable in the Netherlands, thanks largely to the initial popularity of imported ‘perspective’ designs by Jean Cousin and Jacques Androuet du Cerceau, as the collections of Philips II at the Escorial or Ferdinand of Tyrol at Ambras demonstrate. In such collections Vredeman’s works also held an appeal for practicing artists and architects. Vincenzo Scamozzi, for example, owned an album that included plates from Vredeman’s Den Eersten Boek and Das ander Beuch, as well as a complete edition of Architectura. Meanwhile from inventories it is clear that many Dutch 17th century. painters possessed ‘perspectiefboeken’ authored by Vredeman de Vries, specifically. Vredeman and his milieu became relatively unpopular in an atmosphere of architectural classicism after 1700. Only after a re-evaluation of ‘mannerist’ art and architecture had begun among Viennese art historians in the late nineteenth century, and increased authority was granted to the idea of Dutch (and Belgian) national schools was Hans Vredeman de Vries’ work to again receive extensive consideration. In 1870 photolithographic reproductions of several Vredeman volumes from the Brussels library of G.A. van Trigt were published. Soon after monographic treatments by Schoy (1876) and Peters (1895) would independently claim Vredeman as part of divergent architectural heritages, introducing to the artist’s reputation a kind of nationalistic tone which colored his subsequent study. Yet Schoy and Peters also insisted upon Vredeman’s place in the idea of an Netherlandish architectural Renaissance. This idea has influenced many postwar studies of his undertakings, such as Mielke (1967) and Forssman (1956). Meanwhile, Vredeman’s reputation as an indigenously Netherlandish specialist in perspectiven has placed him into many broader discussions about art practice as well as perception and optics, as in Alpers (1983). This at a time when Vredeman’s eccentric reputation has made him again attractive to art- and architectural histories interested in materials traditionally excluded by older stylistic categories.